Efeitos do Programa Bolsa Família na fecundidade das mulheres beneficiárias - Simões, Patrícia (2011)
Among social policies of the new generation, there is the Bolsa Família Program, which acquired the synonym of "instrument for reducing inequality", because it makes a redistribution of income directly from government coffers to the population living in poverty. However, the ambiguity of the theoretical consequences that this type of benefit can have on society emphasizes the importance of scientific studies about this topic. Some questions arise regarding the effectiveness of this kind of policy in socia l change when the approach of this program is done in the context of the demographic transition, in particular the subject of fecundity. By one hand, conditionalities aim investment in human capital, but increasing household income through monetary benefits may encourage the beneficiary families to have more children. We use the theme of income transfer programs, adopting the Bolsa Família Program as main object of study, to investigate the influence of this policy in fecundity rates of the beneficiaries. For this purpose, we use the samples collected by the Demographic and Health Surveys, from MEASURE DHS project, of the years 1991 and 2006. First we make a diference-in-diference to compare the fecundity rates of eligible and ineligible women only for the Northeast region of Brasil. Second, we evaluate the benefit on the beneficiaries fecundity for the Northeast region an also for the whole country. We found positive effects regarding the effectiveness of the program in the reduction of beneficiaries expected fecundity rates when they are compared with those eligible women but not beneficiaries.